Thermal performance of a PCM-filled double-glazing unit with different thermophysical parameters of PCM. (August 2016) - Li, Dong; Li, Zaiwu; Zheng, Yumeng; Liu, Changyu; Hussein, Ahmed Kadhim; Liu, Xiaoyan
Highlights: Thermal performance of phase change material (PCM) double-glazing units was investigated. Thermophysical parameters of PCM play an important role in thermal performance. Increasing density, latent heat, and melting temperature of PCM is an effective method. Melting temperature of 297–299 K is recommended in Daqing, Northeast China. Abstract: Application of phase change material (PCM) in the glazing structure can improve its thermal performance by enhancing its thermal energy storage capacity. In this study, the effect of thermophysical parameters of PCM on thermal performance of a PCM-filled double-glazing unit was investigated. The results show that the temperature time lag of the PCM-filled double-glazing unit increases and the temperature decrement factor decreases with the increase of density, thermal conductivity, specific heat capacity, latent heat, and melting temperature of PCM. Increasing density, latent heat, and melting temperature of PCM are effective to enhance the thermal performance of PCM-filled double-glazed units; however, enhancing thermal conductivity and specific heat capacity are ineffective when thermal conductivity is beyond 2.1 W/(m K) and specific heat capacity is < 4460 J/(kg K).